Metal Oxide and Metal Complex Immobilization Modified Smectite Clay For Green Catalysis and Photo-Catalysis Applications: A Mini Review - Fatimah, Is (Chemistry Department, Universitas Islam Indonesia, 2017)
Clay minerals are promising modifiable material for catalysis application. Fit to green chemistry issue, green catalysis based on clay minerals modification has been designed in our research group. Metal oxide and metal complexes modification onto natural and synthetic smectite clay via pillarization and intercalation processes and its application as green catalyst have been investigated. This paper presents the study on preparation of Ni, Zr and Pt insertion on smectite clay structure for green conversion of citronellal to menthol via catalytic hydrogen transfer mechanism and Ru-complex modified smectite clay as novel photocatalysis application. Effect of clay structure modification was also studied in order to investigate the relationship between physicochemical characteristic change of material modifications and its catalytic/photo-catalytic activity. Some interesting phenomena related to the interaction of metal-clay support for their performance toward reaction kinetics and mechanism are reviewed, with emphasis on the evolution of surface properties and some factors affecting catalytic/photo-catalytic activity